1994
DOI: 10.1111/j.1526-4610.1994.hed3401012.x
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Pain Threshold is Deeply Lowered Far From the Head in Migraine

Abstract: A short-lasting over-distension of the hand-forearm veins, obtained through a non-invasive original maneuver (Hand Arm Vein Distension test) induces local pain when applied to migraine sufferers in inter-critical period. Conversely, subjects with an absolutely negative personal and family history for any type of idiopathic headache do not report any pain or only an uncertain, slight one. The injection of 1 mL of 2% to 8% (i.e. 0.34 mol/L to 1.36 mol/L) hypertonic saline into the antecubital vein during an exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 12 publications
(16 reference statements)
1
13
0
Order By: Relevance
“…The finding that migraineurs were significantly more likely than nonmigraineurs to report chest pain, as well as other categories of pain, is consistent with the theory that migraineurs have a lower pain threshold than nonmigraineurs 7 . Migraineurs have been shown to experience pain to nonpainful stimuli, both during migraine attacks and during intervals between migraine attacks 11,12 . A similar heightened sensitivity to pain has been observed in patients with noncardiac chest pain, which is similar to anginal pain but typically originates from the esophagus 13 …”
Section: Studies Of the Possible Association Between Coronary Heart Dsupporting
confidence: 74%
“…The finding that migraineurs were significantly more likely than nonmigraineurs to report chest pain, as well as other categories of pain, is consistent with the theory that migraineurs have a lower pain threshold than nonmigraineurs 7 . Migraineurs have been shown to experience pain to nonpainful stimuli, both during migraine attacks and during intervals between migraine attacks 11,12 . A similar heightened sensitivity to pain has been observed in patients with noncardiac chest pain, which is similar to anginal pain but typically originates from the esophagus 13 …”
Section: Studies Of the Possible Association Between Coronary Heart Dsupporting
confidence: 74%
“…According to the literature, subjects with tension-type headache exhibit lower cranial PPT (Jensen et al, 1993;Andary et al, 1997;Buchgreitz et al, 2006;Fernández-de-las-Peñas et al, 2007), lower extra-cranial PPT (Nicolodi et al, 1994;Bendtsen, 2000) and normal cranial heat-pain threshold (Ashina et al, 2000;de Tommaso et al, 2003). Therefore, comparisons can be made only with studies conducted on subjects with primary headache or headache following whiplash injury.…”
Section: Discussionmentioning
confidence: 99%
“…The feature is specific to migraine (alias viscerogenic headache) and is not found in healthy subjects or in patients with tension-type headache. The feature is equally present in all patients without regard to age or gender [17].…”
Section: The Relevance Of Chronic Migraine In the Planet Of Chronic Dmentioning
confidence: 71%
“…We observed that the worsening of migraine syndrome is paralleled by an increase in the severity of visceral hyperalgesia [12,13,24] according to different methods. Briefly, in one method, sharp stretching of vein walls is induced by a noninvasive maneuver, while another method refers to the application of an osmotic stimulus to the wall of the vessels [17]. Both methods are based on the application of stimuli which are suited, in nature, to activate polymodal receptors of hollow viscera.…”
Section: S14mentioning
confidence: 99%